Mechanism analysis of a landslide triggered by filling a gully. Issue 5 (6th October 2020) - Xu, Haodi; Shang, Yuequan; Wang, Dongfei; Liu, Zeyong; Sun, Hongyue
Abstract : Construction activities may reduce the stability of slopes by filling at the crown of a landslide, thereby increasing the sliding force. Also, the stability of slopes may be reduced by excavating at the toe of a landslide, thereby reducing the stabilising force. Failure induced by the filling of a natural gully and changing regional hydrogeological conditions have been determined to be the possible causes of the Qili landslide. An analysis of the displacement monitoring data and the safety factor of the landslide indicated that the primary cause of the Qili landslide was an increase in the groundwater level rather than engineering excavation. After analysing the hydrogeological conditions of the region, it was found that the most likely reason for the increase in the groundwater level was the filling of the natural gully. After the gully was full, the only way rainfall could be discharged was through infiltration. As a result of the change in the way the water was discharged, the runoff discharge was reduced, resulting in an increase in the groundwater level. The results of numerical simulation also showed that changes in the discharge conditions would cause an increase in the groundwater level in the landslide area. Therefore, it was determined that the Qili landslide was caused by the filling of the natural gully and that it was a new type of landslide caused by human engineering activities and construction.